The Relationship between Perfectionism with Burnout through Academic Engagement - MH Seif; A Rastgar; R Ershaddi (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī, 2017)
introduction: Today, researchers identified medical students susceptible to burnout that it not only leads to undesirable outcome such as failed, conditional pass, unsuccessful in acquiring necessary specialty even deportation but also, losing physical and moral resources of community. This study examines the impact of perfectionism on academic burnout with the intermediating role of academic engagement among medical students. Methodology: This is a descriptive correlation research which examined on 175 medical students of Shiraz university of Medical sciences in 93-94 that were selected based on Cochran Formula by simple random sampling .Data were selected through Maslach Burnout questionnaire Inventory-Student Survey (2002), Ferasat & colleagues perfectionism scale(1997) and Shaffeli & Bekr Work Engagement Scale for Students (2006). To analyze the data, path analysis and the Pearson correlation coefficient Lisrel and SPSS software were used. Findings: The result indicated that the direct impact of maladaptive perfectionism (0. 24; t = 4.54) adaptive perfectionism (0.-18; t = 3.03) and academic engagement (-0.29; t = 5.86) on academic burnout were respectively, It was also found that perfectionism had indirect impact on academic burnout through academic engagement. Conclusion: based on findings, perfectionism had relationship with academic burnout through academic engagement, it is suggested that authorities train the students to choose their appropriate criteria and help them to maintain their self-esteem if they do not meet these criteria, but they should attempt more to fulfill their logical goals and consequently, experience less burnout and show more engagement.